2016
DOI: 10.1590/1980-5373-mr-2015-0409
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of Martensitic Transformations on Cavitation-Erosion Damage Initiation and Pitting Resistance of a Lean Austenitic Stainless Steel

Abstract: This paper looks into the influences of martensitic transformations on the cavitation-erosion (CE) damage initiation mechanism and pitting corrosion resistance of a lean austenitic stainless steel. The ε and α' martensites are prime sites of CE damage initiation for this steel, whereas grain boundaries are more favourable damage initiation sites for other similar steels. The profusion of ε and α' results in fast surface roughening during the CE process, which may cause a compromise in performance when this ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Passivation metals also have good repassivation performance, meaning that they can carry out repassivation self-repair when their surfaces are damaged, improving service performance in corrosive media [17][18][19][20]. Consequently, passivation metals, especially stainless steels, are widely used in aerospace, nuclear energy, marine and other industrial fields, particularly in the presence of CE, due to their superior corrosion resistance and good mechanical properties [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Passivation metals also have good repassivation performance, meaning that they can carry out repassivation self-repair when their surfaces are damaged, improving service performance in corrosive media [17][18][19][20]. Consequently, passivation metals, especially stainless steels, are widely used in aerospace, nuclear energy, marine and other industrial fields, particularly in the presence of CE, due to their superior corrosion resistance and good mechanical properties [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Westin et al [14] addressed the effects of alloying elements and thermal cycles on the phase balance and microstructure in the high-temperature heat-affected zone of LDX 2101. Recently, Wang and Tavares [15,16] reported that the deformation-induced martensitic transformations could reduce the pitting resistance of LDX. However, studies on the dissolution and precipitation of γ phases in hot working environments and their effects on pitting corrosion in LDX 2101 are lacking.…”
Section: Introductionmentioning
confidence: 99%